Designing a Platform for Flexible and Performant Virtual Routers on Commodity Hardware. - Egi, Norbert; Greenhalgh, Adam; Handley, Mark; Hoerdt, Mickael; Huici, Felipe; Mathy, Laurent; Papadimitriou, Panagiotis (Electronic Communications of the EASST, 2009)
Multi-core CPUs, along with recent advances in memory and buses, render commodity hardware a strong candidate for software router virtualization. In this context, we present the design of a new platform for virtual routers on x86 hardware. We also elaborate on our design choices in order to achieve both high performance and flexibility for packet processing.